LINEARITY OF TEACHERS AND LECTURER'S DIPLOMAS IN INCREASING THE QUALITY OF EDUCATION - Nona Nofiana Samsul; Siti Mayang Sari; Akmaluddin; Jonni Sitorus (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Expressing quality is an absolute and relative concept. Absolute quality is high idealism and must be met, high standards, with high prestigious product characteristics. Relative quality is not an end in itself, but as a means that has been defined or services are assessed, namely whether they meet predetermined standards. Academic qualification is one of the factors to determine a person's expertise in a particular field. Likewise, the linearity of both study and profession is a benchmark for in-depth knowledge and career. The policy regarding diploma linearity is very good, it's just that this policy must be reviewed and explained again to educators, both teachers and lecturers. The purpose of this study is to analyze government policy regarding the linearity of diplomas for both teachers and lecturers in terms of implementation and realization of the goals of the diploma linearity. This research uses a descriptive qualitative approach in the form of a literature study by collecting information from various sources. This study concludes that government policies have been very good at improving the academic qualifications and academic competence of educators, but they are still a frightening specter for educators.